Permafrost degradation and soil erosion as drivers of greenhouse gas emissions from tundra ponds - Vilmantas Prėskienis; Daniel Fortier; Peter M J Douglas; Milla Rautio; Isabelle Laurion (Environmental Research Letters, 2024)
Climate change poses a serious threat to permafrost integrity, with expected warmer winters and increased precipitation, both raising permafrost temperatures and active layer thickness. Under ice-rich conditions, this can lead to increased thermokarst activity and a consequential transfer of soil organic matter to tundra ponds. Although these ponds are known as hotspots for CO _2 and CH _4 emissions, the dominant carbon sources for the production of greenhouse gases (GHGs) are still poorly studied, leading to uncertainty about their positive feedback to climate warming. This study investigates the potential for lateral thermo-erosion to cause increased GHG emissions from small and shallow tundra ponds found in Arctic ice-wedge polygonal landscapes. Detailed mapping of fine-scale erosive features revealed their strong impact on pond limnological characteristics. In addition to increasing organic matter inputs, providing carbon to heterotrophic microorganisms responsible for GHG production, thermokarst soil erosion also increases shore instability and water turbidity, limiting the establishment of aquatic vegetation—conditions that greatly increase GHG emissions from these aquatic systems. Ponds with more than 40% of the shoreline affected by lateral erosion experienced significantly higher rates of GHG emissions (∼1200 mmol CO _2 m ^−2 yr ^−1 and ∼250 mmol CH _4 m ^−2 yr ^−1 ) compared to ponds with no active shore erosion (∼30 mmol m ^−2 yr ^−1 for both GHG). Although most GHGs emitted as CO _2 and CH _4 had a modern radiocarbon signature, source apportionment models implied an increased importance of terrestrial carbon being emitted from ponds with erosive shorelines. If primary producers are unable to overcome the limitations associated with permafrost disturbances, this contribution of older carbon stocks may become more significant with rising permafrost temperatures.